Pengembangan Media Pembelajaran Diorama pada Mata Pelajaran IPAS Materi Metamorfosis Kelas III SDN 1 Lembahsari Tahun Ajaran 2025/2026 - Rizkawati; Muhammad Erfan; Fitri Puji Astria (Mataram University, 2026)
This study aimed to develop a diorama learning media for the Science and Social Studies (IPAS) subject on the topic of metamorphosis for third-grade students at SDN 1 Lembahsari and to determine its feasibility and practicality. The study was motivated by the limited use of instructional media capable of visualizing the metamorphosis process concretely, making it difficult for students to understand the concept. The developed product was a metamorphosis diorama equipped with a wooden storage box and a user guide. This research employed the Research and Development (R&D) method using the Sugiyono (2013) development model. The research stages included identifying potential and problems, data collection, product design, design validation, design revision, product testing, product revision, and final product development. The research subjects consisted of the third-grade teacher and students of SDN 1 Lembahsari. Data were collected through validation questionnaires completed by media experts and material experts, as well as response questionnaires from teachers and students. The collected data were analyzed using descriptive quantitative analysis. The results indicated that the developed diorama learning media achieved a feasibility score of 93.75% from the media expert and 88.8% from the material expert, both categorized as very feasible. The practicality test showed a teacher response score of 94.6% and a student response score of 96.93%, both categorized as very practical. Therefore, the developed diorama learning media on metamorphosis is considered feasible and practical for use in Science and Social Studies (IPAS) learning for third-grade elementary school students.